2017
DOI: 10.15446/rev.colomb.biote.v19n2.60405
|View full text |Cite
|
Sign up to set email alerts
|

Respuesta de cultivares de Musa spp. al estrés hídrico in vitro inducido con polietilenglicol 6000

Abstract: Respuesta de cultivares de Musa spp. al estrés hídrico in vitro 75Respuesta de cultivares de Musa spp. al estrés hídrico in vitro inducido con polietilenglicol 6000Responses of Musa spp. cultivars to in vitro water stress induced with polyethylene glycol 6000 RESUMEN Los plátanos y bananos son cultivos sensibles al déficit hídrico. Las sequías cada vez más prolongadas sugieren la necesidad de obtener plantas tolerantes a este factor; la selección temprana de estas plantas, comparada con la selección en campo, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 29 publications
1
1
0
Order By: Relevance
“…It was found that the highest content of total sugars and chlorophyll levels were in SV 25VS1 with 71.55 mg equivalent to glucose/g dry vegetable and 425.35 mg m -2 (table 3 and figure 3), which corresponds to the first SV planted in the culture medium MS + ANA + BAP + PEG 25 g•L -1 , a medium with high levels of water retention. Similar results are reported by Moreno-Bermúdez et al, (2017), who found high levels of chlorophyll in in-vitro banana seedlings submitted to water deficit using PEG (Table 3).…”
Section: Resultssupporting
confidence: 90%
“…It was found that the highest content of total sugars and chlorophyll levels were in SV 25VS1 with 71.55 mg equivalent to glucose/g dry vegetable and 425.35 mg m -2 (table 3 and figure 3), which corresponds to the first SV planted in the culture medium MS + ANA + BAP + PEG 25 g•L -1 , a medium with high levels of water retention. Similar results are reported by Moreno-Bermúdez et al, (2017), who found high levels of chlorophyll in in-vitro banana seedlings submitted to water deficit using PEG (Table 3).…”
Section: Resultssupporting
confidence: 90%
“…In recent years, betalains have received a renewed interest due to their physicochemical characteristics (high stability at wide ranges of temperature and pH) that can be of utility in many industries, as well as bioactive compounds for the prevention of some diseases [ 25 , 26 , 27 , 28 ]. Betalains are nitrogenous phenolic compounds derived from tyrosine and are exclusive to the order Caryophyllales.…”
Section: Discussionmentioning
confidence: 99%